The Immune Response Is Involved in Atherosclerotic Plaque Calcification: Could the RANKL/RANK/OPG System Be a Marker of Plaque Instability? - Fabrizio Montecucco; Sabine Steffens; François Mach (Clinical and Developmental Immunology)
Atherogenesis is characterized by an intense inflammatory process, involving immune and vascular cells. These cells play a crucial role in all phases of atherosclerotic plaque formation and complication through cytokine, protease, and prothrombotic factor secretion. The accumulation of inflammatory cells and thus high amounts of soluble mediators are responsible for the evolution of some plaques to instable phenotype which may lead to rupture. One condition strongly associated with plaque rupture is calcification, a physiopathological process orchestrated by several soluble factors, including the receptor activator of nuclear factor NFκB ligand (RANKL)/receptor activator of nuclear factor NFκB (RANK)/osteoprotegerin (OPG) system. Although some studies showed some interesting correlations with acute ischemic events, at present, more evidences are needed to evaluate the predictive and diagnostic value of serum sRANKL and OPG levels for clinical use. The major limitation is probably the poor specificity of these factors for cardiovascular disease. The identification of tissue-specific isoforms could increase the importance of sRANKL and OPG in predicting calcified plaque rupture and the dramatic ischemic consequences in the brain and the heart.